Arthroscopic Lesser Trochanter Osteoplasty, Quadratus Femoris Debridement, and Sciatic Neurolysis via Posterior Approach for Ischiofemoral Impingement - Zhang, Qingguo; Han, Dawei; Ying, Liwei; Ye, Lingchao; Yang, Xiangdong; Liu, Peihong; Zhou, Xiaobo; Tung, Tao-Hsin (Frontiers in Surgery, 2022)
Ischiofemoral impingement (IFI) syndrome is considered the narrowing of the ischiofemoral space, leading to pathological changes in the quadratus femoris and sciatic nerve, causing posterior hip and sciatica-like pain. Open or arthroscopic resection of the lesser trochanter to enlarge the ischiofemoral space is the main surgical procedure. However, there is a lack of research on isolated IFI, and currently known surgical procedures are at risk of weakening the flexion strength of the hip joint. In this study, four patients, who were diagnosed with isolated IFI and had undergone arthroscopic treatment with partial resection of the lesser trochanter, debridement of the quadratus femoris, and decompression of the sciatic nerve, were reviewed. To the best of our knowledge, this is the first study to describe the management of IFI using a series of surgical procedures via a posterior approach as an effective treatment option. The outcomes of this study broadened the strategies for IFI management.